2019
DOI: 10.1515/nanoph-2019-0035
|View full text |Cite
|
Sign up to set email alerts
|

Monolithic waveguide laser mode-locked by embedded Ag nanoparticles operating at 1 μm

Abstract: Monolithic waveguide laser devices are required to achieve on-chip lasing. In this work, a new design of a monolithic device with embedded Ag nanoparticles (NPs) plus the Nd:YAG ridge waveguide has been proposed and implemented. By using Ag+ ion implantation, the embedded Ag NPs are synthesized on the near-surface region of the Nd:YAG crystal, resulting in the significant enhancement of the optical nonlinearity of Nd:YAG and offering saturable absorption properties of the crystal at a wide wavelength band. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 58 publications
1
23
0
Order By: Relevance
“…Later, rapid development has been achieved in the laser field based on the embedded NPs in dielectrics. [ 8,153,184–187 ] Nie et al reported the Q‐switched laser generation in visible light band using Nd:YAG crystal with Au NPs embedded. [ 8 ] Enhanced saturable absorption at visible light band was found and utilized for Q‐switching operation.…”
Section: Selected Photonic Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Later, rapid development has been achieved in the laser field based on the embedded NPs in dielectrics. [ 8,153,184–187 ] Nie et al reported the Q‐switched laser generation in visible light band using Nd:YAG crystal with Au NPs embedded. [ 8 ] Enhanced saturable absorption at visible light band was found and utilized for Q‐switching operation.…”
Section: Selected Photonic Applicationsmentioning
confidence: 99%
“…Considering the fact that Nd:YAG crystal is traditional laser crystal, monolithic waveguide laser device was fabricated by embedded Ag NPs based on Nd:YAG crystal. [ 184 ] Efficient Q‐switched mode‐locked laser with the minimum pulse width of 29.5 ps and maximum repetition rate of 10.53 GHz was obtained under the excitation of 810 nm. It should be noted that the measured pulse width shows significant potential for further optimization owing to the ultrafast nonlinear optical response with the relaxation time in the femtosecond scale.…”
Section: Selected Photonic Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main challenge of SiO 2 glass as SAs is the low third‐order optical nonlinearity, which requires significant enhancement and further modulation to achieve adequate NLO response. Recently, noble metallic NPs have attracted renewed interest in the field of ultrafast pulse generation . Owing to the fascinating localized surface plasmon resonance (LSPR) effect, plasmonic NPs have showed exceptional abilities to modulate the NLO response of dielectric optical materials .…”
Section: Information About Sample Preparationmentioning
confidence: 99%
“…As shown in figure 3, the embedded plasmonic nanoparticles could enable the highly integrated design of pulsed waveguide laser sources. Through the evanescent-field interaction modulation, QML waveguide laser operating at 1 µm is obtained with 10.53 GHz repetition rate and 29.5 ps pulse width [89]. Another intriguing example is that the giant enhancement of optical nonlinearity can be achieved in fused silica by tuning the interparticle spacing of embedded nanoparticle array.…”
Section: Mode-locked Waveguide Lasersmentioning
confidence: 99%